REKAYASA MODEL PENGUATAN KESIAPAN KERJA LULUSAN PENDIDIKAN VOKASI (Studi pada SMK di Kota Semarang) - Rauly Sijabat (STIE Pelita Nusantara Semarang, 2018)
The study of job readiness has been widely researched but is still an interesting topic given the empirical phenomenon which indicates the low level of work readiness. In addition, the findings from the studies that have been conducted on explanatory variables of work readiness are also not conclusive. Departing from this phenomenon, the study again developed a research model that